APPLICATION PROCEDURE OF INTERNATIONAL FINANCIAL REPORTING STANDARDS IN BUSINESS ENTITIES (American Journal of Business Management, Economics and Banking, 2025)
The main purpose of international standards in financial reporting is to bring the financial information of enterprises in different countries into a comparable, reliable, and transparent form. This article outlines the content of International Financial Reporting Standards (IFRS), the principles of their formation, and the mechanisms of their practical application. In addition, the views of domestic and foreign researchers on the topic are summarized, and relevant recommendations are provided.